2017
DOI: 10.1186/s12936-017-1978-6
|View full text |Cite
|
Sign up to set email alerts
|

Do the venous blood samples replicate malaria parasite densities found in capillary blood? A field study performed in naturally-infected asymptomatic children in Cameroon

Abstract: BackgroundThe measure of new drug- or vaccine-based approaches for malaria control is based on direct membrane feeding assays (DMFAs) where gametocyte-infected blood samples are offered to mosquitoes through an artificial feeder system. Gametocyte donors are identified by the microscopic detection and quantification of malaria blood stages on blood films prepared using either capillary or venous blood. However, parasites are known to sequester in the microvasculature and this phenomenon may alter accurate dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
6
22
1
Order By: Relevance
“…ovale targets using the GFP assay. These results are in line with several previous studies that also found no differences in parasite density or diagnostic sensitivity between capillary and venous samples [10,12,13]. However, our data have shown that the GFP assays has significantly higher sensitivity for detection of Plasmodium spp.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…ovale targets using the GFP assay. These results are in line with several previous studies that also found no differences in parasite density or diagnostic sensitivity between capillary and venous samples [10,12,13]. However, our data have shown that the GFP assays has significantly higher sensitivity for detection of Plasmodium spp.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas most other studies emphasized testing of children or young teens [4,10,11,13,14], our study population was significantly older, with a median of 27 years and 25% of the tested subjects between 21 and 25 years of age. It is possible that age-related physiological differences may affect the parasite's lifecycle, its clinical presentation, and potentially even its prevalence within various compartments [23][24][25].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This phenomenon, well demonstrated for a range of helminths (1518) and protozoic trypanosomes (14), has remained speculative for Plasmodium parasites (22). Two recent studies in Cameroonian parasite carriers that used microscopy as diagnostic tool yielded conflicting results: one observed higher P. falciparum parasite prevalence in finger prick capillary blood compared to venous blood from hospital patients (36), the other found no differences for asexual parasites or gametocytes in gametocyte carriers (37). The utility of finger prick blood to estimate parasite biomass in skin tissue is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the spatial distribution of mature gametocytes in the bloodstream, a handful of studies have compared their density between venous and capillary blood. A majority of them have found a higher density of gametocytes in capillary than in venous blood ((2933) but see (34, 35)). However, comparisons of the number of gametocytes from the same blood compartment (veins or capillaries) but from different body parts has been investigated in a unique study conducted in 1952, where a 3-fold higher prevalence of gametocytes in skin capillary blood compared to thick smears prepared from finger-prick has been observed (36).…”
Section: Introductionmentioning
confidence: 99%